Comment on "Semiempirical potentials for positron scattering by atoms" - Sullivan, J; Machacek, J; Buckman, S; Bray, Igor (American Physical Society, 2012)
In their recent paper, Assafräo et al. [ D. Assafräo, H. R. J. Walters, F. Arretche, A. Dutra and J. R. Mohallem Phys. Rev. A 84 022713 (2011)] use a scaled adiabatic potential to calculate total and differential cross sections for positron scattering from a variety of targets. They claimed that the results are “very close to experimental and best theoretical data.” A brief examination of the recent literature on this subject demonstrates, however, that comparisons with several important and recent results have not been made, and that such comparisons clearly affect the accuracy of their conclusions.